The Story of the paddle steamer - Dumpleton, Bernard (Venton, 2002)
The paddle steamer holds a unique place in the history of maritime engineering. When the engineers of the early nineteenth century experimented with steamboats they chose the paddle wheel as the form of propulsion. Within twenty years the paddle steamers were at work on inland waters and short sea passages. They were graceful, elegant ships, but in the jet age too slow and uneconomical. In the 1950s they went to the breaker's yards in droves, and now there are only a few left. This book tells they story of the paddle steamers, and of the men who built, owned and sailed them.